Speech acts and the communicative functions of emojis in LIHKG online discussion forum amid COVID-19 - Yu, Carol; Tay, Dennis; Jin, Ying; Yuan, Xinhua (Frontiers in Psychology, 2023)
Since the beginning of 2022, the Hong Kong government has imposed strict social distancing measures and changed its stance on various regional policies with the aim to contain the so-called ‘fifth wave’ of Covid-19. In these pandemic and ‘infodemic’ times filled with uncertainty and fear, Hong Kong netizens used local online discussion forums as a resource to establish an innovative form of ‘helping network’. This study is based on 230 posts from a popular local online discussion forum ‘LIHKG’ in February 2022 when the pandemic was regarded as most critical by the Department of Health. Speech Acts theoretic approach was adopted to explore how forum users employed speech acts to perform various communicative practices such as expressing concerns, asking for information, and engaging with others in a CMC environment amid a global health crisis. Representatives were found to be the most dominant text-based speech acts, followed by directives, expressives and commissives. Speech acts provide forum users a context in which emoji usage occurs. Forum users not only make use of words to ‘do’ things in the online self-help forum, but they also employ emojis to either supplement or complement speech acts. This study also shows that emojis perform multiple functions in the discussion posts and argues that they do not merely function as emotion indicators of their textual company, but also carry significant pragmatic meanings by illustrating how they can also carry illocutionary force and in some cases, even alter the illocutionary force of their preceding texts. The findings of this study enhance our understanding of how forum users communicate via verbal and nonverbal means within the underexplored ‘helping domain’ of online discussion forums. It also suggests that online discussion forum interactions need to be approached differently than other better understood alternatives.